Multi-Level approach for the analysis of water effects in corn flakes - Farroni, Abel Eduardo (2008)
The purpose of this work was to analyze the effect of water on thermal transitions, mechanical properties, and molecular mobility in corn flakes (CF), and their relationships. Commercial common (CCF) and sugar-frosted (SCF) corn flakes were studied in a water content (wc) range from 5 to 20 (% dry basis). The slope of 1H NMR spin−spin relaxation time T2* (determined by FID) versus temperature plot changed close to Tg. Compression force showed a maximum at wc of ca. 12 and 16% (db) for SCF and CCF, respectively. 1H NMR complemented DSC data in determining the temperature dependence of water and solid mobility, in order to assess quality of laminated corn products. The results of the present work indicate that while the compression force showed a maximum value as a function of water content, Tg values determined by DSC or by spin−spin relaxation decreased progressively with increasing water content.